2013
DOI: 10.1093/pcp/pct129
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Polysaccharides are Mislocalized to the Vacuole in echidna Mutants

Abstract: During cell wall biosynthesis, the Golgi apparatus is the platform for cell wall matrix biosynthesis and the site of packaging, of both matrix polysaccharides and proteins, into secretory vesicles with the correct targeting information. The objective of this study was to dissect the post-Golgi trafficking of cell wall polysaccharides using echidna as a vesicle traffic mutant of Arabidopsis thaliana and the pectin-secreting cells of the seed coat as a model system. ECHIDNA encodes a trans-Golgi network (TGN)-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Previous studies of gnl1 and ech mutants have revealed altered ER morphology (Nakano et al, 2009;McFarlane et al, 2013), similar to the localization pattern of the ER membrane-localized CER2-GFP in gnl1-1 and ech (Supplemental Fig. S7).…”
Section: Defects In Er Morphology Are Correlated With Wax Biosynthesisupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies of gnl1 and ech mutants have revealed altered ER morphology (Nakano et al, 2009;McFarlane et al, 2013), similar to the localization pattern of the ER membrane-localized CER2-GFP in gnl1-1 and ech (Supplemental Fig. S7).…”
Section: Defects In Er Morphology Are Correlated With Wax Biosynthesisupporting
confidence: 75%
“…Both ech and trs120-4 are defective in TGN protein complexes. ECH is a part of the ECH/Ypt/Rab-interacting protein complex, which is required specifically for the trafficking of secretory vesicles from the TGN to the plasma membrane (Gendre et al, 2011;Boutté et al, 2013;McFarlane et al, 2013). ech is a null allele (Gendre et al, 2011), while null alleles of trs120 (trs120-2 and trs120-3) are seedling lethal (Thellmann et al, 2010;Qi et al, 2011); therefore, experiments on mature plants required use of the weaker allele, trs120-4.…”
Section: Secretion Mutants Display Defects In Cuticular Wax Load On Tmentioning
confidence: 99%
“…GNL1 is required for coat protein complex I vesicle formation in retrograde trafficking from the Golgi to the ER [46]. ECHIDNA (ECH) is a part of the ECH/Rab GTPase-interacting protein complex required for vesicle trafficking from the TGN to the PM [68][69][70]. Transport particle protein subunit120-4 (TRS120-4) is a part of the large GTPase complex required for secretion to the cell wall and cell plate [71,72].…”
Section: Co-migration Of Transporters With Membrane Vesiclesmentioning
confidence: 99%
“…VHA-a1 has previously been connected to the secretion of BRI1 (Dettmer et al, 2006). However, despite the colocalization between ECH and VHA-a1 at the TGN as well as the mislocalization of VHA-a1 in the ech mutant, ECH-dependent AUX1 secretory trafficking in the apical hook and ECH-dependent pectin secretion in seed coat cells occur independently of VHA-a1 (Boutté et al, 2013;Gendre et al, 2013;McFarlane et al, 2013). Like ECH, BIGs (BIG3/4) localize to the TGN and colocalize with VHA-a1 (Richter et al, 2014) (Figures 6C and 6D) and ECH ( Figures 6A and 6D).…”
Section: Big1-4 Mediate Aux1 Trafficking To the Pm At An Echpositive mentioning
confidence: 98%